Inner Ear Proteins as Potential Biomarkers. Issue 2 (February 2020) - Mulry, Erin; Parham, Kourosh
Abstract : Objective: The purpose of this manuscript is to identify proteins exclusive to the inner ear based on published research to identify potential candidate biomarkers and guide future inner ear research. Data Sources: Literature on inner ear proteins published on Pubmed, Google Scholar, and Scopus was reviewed using key words such as "inner ear molecule, " "inner ear exclusive protein, " and several specific protein searches such as "prestin" based on findings from the initial searches. Study Selections: Studies were selected for abstract review based on title relevance, and full text was chosen for review based on abstract relevance. Several related studies cited in initially reviewed literature were also chosen to compile more detailed information on specific molecules with the goal of at least two to three published articles for each protein. Data Extraction & Synthesis: Proteins that were cited to have only been found within the inner ear were included in this review, including some proteins that were later identified outside the inner ear. Information regarding their size, location, function, and clinical significance was recorded. Conclusions: Based on this literature search, eight proteins exclusive to the inner ear were identified including otolin-1, otoconin 90/95, prestin, otoancorin, otogelin, α-tectorin, β-tectorin, and cochlin. Proteins initially found to be exclusive to the inner ear though later identified outside of the inner ear included oncomodulin, otospiralin, and otoraplin. This literature review may serve as a focused guide for future research on proteins exclusive to the inner ear as potential biomarkers for diseases of the inner ear.